A Systematic Review of the Effect of Vitamin C When Given Orally as a Secondary Prevention Method to Patients With Established Cardiovascular Disease or Those at Very High Risk of Developing Cardiovascular Disease. - Whitmore, Amelia (2009)
Introduction and Background. Cardiovascular disease is the main cause of death in the UK and is responsible for almost 198,000 deaths every year (British Heart Foundation 2008a) therefore it is important that prevention is achieved. This review has demonstrated that research in to secondary prevention of cardiovascular disease by vitamin C is limited and systematic reviews on the subject have also been limited. The Review Question. To what extent is secondary prevention successful when vitamin C is given orally as an intervention to patients with established cardiovascular disease or patients at very high risk of developing cardiovascular disease? Methods. An electronic literature search was carried out according to a strict search strategy and those studies that satisfied the inclusion and exclusion criteria then underwent a quality assessment. Synthesis of the data was done by putting the results of the studies in to tables and text according to nine outcomes: cardiac death, myocardial infarction, stroke, hypertension, serum cholesterol levels, atherosclerosis progression, peripheral disease, angina and heart failure. Results and Conclusions. Four of the studies that found beneficial effects were of poor quality and considerable heterogeneity existed between the studies. The review concluded that although some studies showed benefit, the poor quality and heterogeneity that existed warrants further research to be carried out before the introduction of vitamin C in to practice for secondary prevention of cardiovascular disease is warranted.